2013
DOI: 10.15376/biores.8.4.6136-6150
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ligninolytic Enzymes by Newly Isolated Bacteria from Palm Oil Plantation Soils

Abstract: Three aerobic lignin-degrading bacterial strains were isolated from palm oil plantation soils. The bacterial isolates were screened using a selective nutrient medium of minimum salt media (MSM), with kraft lignin as lignin substrate and methylene blue as the ligninolytic dye indicator. The newly isolated bacterial strains SHC1, SHC2, and SHC3 were found to have the potential to tolerate high concentrations of kraft lignin and produced all three main ligninolytic enzymes (lignin peroxidase, manganese peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Traditionally, lignin-degrading microorganisms have been selected based on qualitative methods such as direct screening using culture plates from environmental samples or by first enriching the environmental samples and then performing a plate-based screening [ 27 ]. The conventional screening process followed in previous studies is illustrated in the steps (left) shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, lignin-degrading microorganisms have been selected based on qualitative methods such as direct screening using culture plates from environmental samples or by first enriching the environmental samples and then performing a plate-based screening [ 27 ]. The conventional screening process followed in previous studies is illustrated in the steps (left) shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leucobacter sp. has been described as capable to degrade hydrocarbons in polluted soil (Brzeszcz et al, 2020) and reported for its ligninolytic activity (Rahman et al, 2013), moreover involved in nitrogen cycle in soil (Solanki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Later, this ingested compound is internalized and eventually degraded by different enzymes. Bacteria-derived ligninolytic laccase enzymes catalyze the mono-electronic oxidation of substrates and degrade a wide spectrum of pollutants from factories (Rahman et al, 2013). Till date, various bacterial strains have been isolated showing varying capabilities for the dissolution of varied pollutants or heavy metals; thus, it is necessary to identify a single bacterial strain capable of reducing the majority of pollutants as well as heavy metals.…”
Section: Chettri Et Al (2021)mentioning
confidence: 99%